Classification of modulated motor cortex based on Anodal and Cathodal tDCS - Chowdhury, Zarif Ahmed; Alam, Dewan Nahidul; Nahid, Md. Abu Fattah Hossain Bhuiyan (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.